Youth and disaster management in Malaysia - Abdul Rahman, Haliza (Human Resource Management Academic Research Society, 2020)
Introduction: Malaysia is facing increasing exposure to disaster risk. In the last two decades from 1998 until 2019, Malaysia also has experienced 51 natural disaster events, with 281 deaths, over 3 million people affected, and damages worth nearly US$2 billion (MYR8 billion). Thus, disaster management has become a significant concern of the Malaysian government. Two examples of environmental disasters in Malaysia have been discussed. Objective: The objective of this paper is to highlight the importance of youth involvement in disaster risk management, identify strategies to effectively involve them in disaster risk management as well as the describe the current roles of the Malaysian youth in disaster risk management. Method: This review was carried out using secondary data collected from multiple sources on the topic roles of youth in disaster preparedness, risk reduction, and management from the year of 2008-2018. Result: With the considerable youth population in Malaysia, youths of today must be empowered with the knowledge needed to cope with the adverse effects of natural disasters. Furthermore, they are physically strong, mentally agile, and look for change and dynamism in their own lives and their communities. They also embody power and strength, are idealistic, and accept new ideas and views without much hesitation. Therefore, youth could play an essential role in disaster risk reduction and management to decrease the number of victims and casualties. Conclusion: Youth are the best people to participate in disaster management issues because they are invaluable human resources of every nation.